2018
DOI: 10.1016/j.jid.2017.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Incident Liver Disease in Patients with Psoriasis, Psoriatic Arthritis, and Rheumatoid Arthritis: A Population-Based Study

Abstract: Relatively little is known about the risk for incident liver disease in psoriasis (PsO), psoriatic arthritis (PsA), and rheumatoid arthritis (RA). We performed a cohort study among patients with PsO, PsA, or RA and matched controls in The Health Improvement Network from 1994 to 2014. Outcomes of interest were any liver disease, nonalcoholic fatty liver disease, and cirrhosis (any etiology). Among patients with PsO (N = 197,130), PsA (N = 12,308), RA (N = 54,251), and matched controls (N = 1,279,754), the adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 49 publications
2
77
0
5
Order By: Relevance
“…Liver fibrosis is a wound‐healing response that occurs secondary to insults from hepatocyte lipid accumulation, inflammation and exposure to toxins, such as methotrexate and alcohol. A 2017 population‐based study (people with psoriasis: n = 197 130) supported what other studies have previously shown: people with severe psoriasis are more likely to have liver fibrosis and cirrhosis than age‐, sex‐ and BMI matched controls in the general population …”
supporting
confidence: 71%
“…Liver fibrosis is a wound‐healing response that occurs secondary to insults from hepatocyte lipid accumulation, inflammation and exposure to toxins, such as methotrexate and alcohol. A 2017 population‐based study (people with psoriasis: n = 197 130) supported what other studies have previously shown: people with severe psoriasis are more likely to have liver fibrosis and cirrhosis than age‐, sex‐ and BMI matched controls in the general population …”
supporting
confidence: 71%
“…Eight case-control studies [2][3][4][5][6][7]9,10 and one prospective cohort study 8 with a total of 3 019 308 patients were identified to compare the risk of non-alcoholic fatty liver disease in psoriatic and nonpsoriatic patients. Unadjusted metaanalysis demonstrated a two times increased risk of nonalcoholic fatty liver disease in psoriatic patients compared to nonpsoriatic patients (OR 2.01, 95% CI 1.48-2.73, I 2 = 91%, P < 0.00001).…”
Section: E352mentioning
confidence: 99%
“…Impaired hepatic function is documented in up to 6% of patients with RA, emerging with abnormal elevations of alkaline phosphatase, bilirubin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), and serum gamma‐glutamyltransferase and low albumin levels . Abnormal liver function has also been attributed to use of disease‐modifying antirheumatic drugs, which are commonly used for treatment of immune‐mediated inflammatory diseases …”
mentioning
confidence: 99%
“…18,21,22 Abnormal liver function has also been attributed to use of disease-modifying antirheumatic drugs, which are commonly used for treatment of immune-mediated inflammatory diseases. 23 Because of the contribution of CYP metabolism to upadacitinib clearance, it is important to characterize the impact of hepatic impairment on upadacitinib pharmacokinetics to inform if dose adjustments are required. The objective of this study was to evaluate the pharmacokinetics and safety of upadacitinib following administration of a single dose in subjects with mild and moderate hepatic impairment (according to the Child-Pugh classification) compared with subjects with normal hepatic function.…”
mentioning
confidence: 99%